PENGARUH INDUKSI GONADOTROPIN RELEASING HORMONE TERHADAP KADAR HEMATOLOGIS PADA DOMBA BATUR - Rabbani, Alief; Sumaryadi, Mas Yedi; Setyaningrum, Agustinah (ANGON: Journal of Animal Science and Technology, 2022)
Background. This study aims to determine the effect of Induction gonadotropin releasing hormone hematological levels in Batur sheep which include the levels of erythrocytes (SDM), leukocytes (SDP), and hemoglobin. Materials and Methods. The research material used was 20 female Batur ewes with a minimum parity of 2 times and an average age of 3 years, then grouped into two groups of 10 each. The research method used is experimental methods in the field which are grouped into 2 (two) treatment groups, namely: P1 =Double injection of PGF2? (Dinoprost trometamol 5mg/ml) as much as 2 ml intramuscularly as a controland P2= Double injection of PGF2? (Dinoprost trometamol 5mg/ml) as much as 2 ml intramuscularly as a control plus 1 ml of gonadotropin releasing hormone (Gonadorelin 0.1 mg/ml) intramuscularly. Each treatment was repeated 10 times. Blood sample were taken as much as 2-4 ml through the jugular vein with a 5 cc syringe. Data was processed using unequal t-test. Results. The results of statistical analysis showed that there was a very significant difference (P<0.01) from injection of gonadotropin releasing hormone to leukocyte levels in Batur sheep, whereas there was no significant difference in erythrocyte and hemoglobin levels (P>0.05) and was still relatively normal. Conclusion. The induction of gonadotropin releasing hormone did not increase the levels of erythrocytes and hemoglobin but there was an increase in leukocytes that exceeded the normal limit, so the dose of GnRH should be adjusted according to the body weight of the livestock.